Acetylated Thioredoxin Reductase 1 Resists Oxidative Inactivation - Wright, David. E.; Panaseiko, Nikolaus; O’Donoghue, Patrick (Frontiers in Chemistry, 2021)
Thioredoxin Reductase 1 (TrxR1) is an enzyme that protects human cells against reactive oxygen species generated during oxidative stress or in response to chemotherapies. Acetylation of TrxR1 is associated with oxidative stress, but the function of TrxR1 acetylation in oxidizing conditions is unknown. Using genetic code expansion, we produced recombinant and site-specifically acetylated variants of TrxR1 that also contain the non-canonical amino acid, selenocysteine, which is essential for TrxR1 activity. We previously showed site-specific acetylation at three different lysine residues increases TrxR1 activity by reducing the levels of linked dimers and low activity TrxR1 tetramers. Here we use enzymological studies to show that acetylated TrxR1 is resistant to both oxidative inactivation and peroxide-induced multimer formation. To compare the effect of programmed acetylation at specific lysine residues to non-specific acetylation, we produced acetylated TrxR1 using aspirin as a model non-enzymatic acetyl donor. Mass spectrometry confirmed aspirin-induced acetylation at multiple lysine residues in TrxR1. In contrast to unmodified TrxR1, the non-specifically acetylated enzyme showed no loss of activity under increasing and strongly oxidating conditions. Our data suggest that both site-specific and general acetylation of TrxR1 regulate the enzyme’s ability to resist oxidative damage.